Virtual reality-based collaborative design method for designing customized garment for disabled people with scoliosis. Issue 2 (18th April 2017) - Hong, Yan; Bruniaux, Pascal; Zeng, Xianyi; Liu, Kaixuan; Chen, Yan; Dong, Min
Abstract : Purpose: The purpose of this paper is to present a new collaborative design-based method for designing customized garments, aimed at the physically disabled people with scoliosis. Design/methodology/approach: The proposed method is based on the virtual human model created using a 3D body scanner, permitting to simulate the consumer's morphological shape with atypical physical deformations. Next, customized 2D and 3D virtual garment prototyping tools will be used to create products through interactions between the consumer, designer and pattern maker. The general principle of the proposed design method is based on the following sequence: design-display-evaluation-adjustment. After running the sequence for a number of times, the final design solution, which will be approved by both the designer and consumer, can be easily identified. Findings: Design knowledge, which is already applied to normal body shapes successfully can be applied to 3D garment design using the concept which is based on collaborative design. Through this process, the classical 2D garment design knowledge, especially 2D patterns and design rules, can be modified and applied according to a normalized virtual garment sensory evaluation procedure quantitatively. This evaluation procedure, interactively performed by the designer and consumer, can permit to adapt the finished product to disabled people afflicted with severe scoliosis. The proposed method is also validated to be more advanced compared to 2D-to-3D virtual CAD design method, especially for atypical morphologies. Originality/value: As a co-design method, 3D virtual draping and sensory evaluation can fully satisfy the interaction between the garment design technical space and perceptual space of the finished garments ensuring desired 3D garment fit effect by adjustment of technical parameters. 3D scanning technology is used to generate a complete digitalized 3D human model, permitting to extract the main features of body shapes without accurate measurements. As a knowledge-based design process, both the fashion design knowledge and the pattern making knowledge will be extracted to provide inspirations and references. Successful design solutions will be incorporated into the fashion design knowledge base in order to generate new design rules and enhance professional design knowledge.